Chính sách thu hút và hỗ trợ sinh viên sư phạm tại Việt Nam hiện nay: Thực trạng và giải pháp - Phạm Hải Hà, Phạm Hải Hà; Nguyễn Anh Tuấn, Nguyễn Anh Tuấn (Tạp chí Giáo dục, 2026)
In the context of reform and the implementation of the 2018 General Education Program, the need for a large and high-quality teaching staff, along with a balanced structure, has become a strategic issue for Vietnam. However, for many years, the teaching profession has no longer been a priority for many academically strong students; entrance scores may be significantly lowered in some teacher training programs and schools, while many others face teacher shortages. Based on the theoretical framework of human resource attraction policies, international experience in teacher development, and an analysis of current policies, this study clarifies the current state of policy implementation in Vietnam. The results show that policies have created certain positive effects in attracting students and enrollment, but many challenges still exist that reduce the effectiveness of these policies. Therefore, solutions are proposed with the expectation of contributing to enhancing the attractiveness of the profession, attracting and retaining high-quality human resources for Vietnam’s education sector in the coming period.